Improving Quality of Life in Mitch Albom's Memoir: Tuesdays with Morrie: An Old Man, A Young Man, and Life's Greatest Lesson (2006): Humanistic Psychological Perspectives - Prajayani, Sevina Anindia, Dr. M. Thoyibi, M.S (2017)
This research is about the improving quality of life in Mitch Albom memoir in the TUESDAYS WITH MORRIE (2006) which analyzed based on Humanistic Psychological Perspectives. The aims of this study was to identified the indicators in quality of life, to describe the portrayal of improving quality of life in this memoir, and to defined the reason of the author address quality of life as the issue in Tuesdays with Morrie (2006). The primary data source was the memoir by Morrie Albom, Tuesdays with Morrie which announced 1997. The secondary data source was from several sources, such as: the author's biography, E-books, text of interview, and another references to support the analysis. The result of this study are: firstly, the indicators which described improving quality of life in the memoir. Secondly, show the portrayal of the issue in the memoir. Thirdly, showed that there was reason from the author to make people realized about importance to improve the quality of life, especially people who was suffered.